0.35μm SPDT RF CMOS switch for wireless communication application - Bambang Soeroso, Iksannurazmi; Nordin, Anis Nurashikin; Alam, A. H. M. Zahirul (2013)
In recent years, wireless communication particularly in the front-end transceiver architecture has increased its functionality. This trend is continuously expanding and of particular is reconfigurable radio frequency (RF) front-end. A multi-band single chip architecture which consists of an array of switches and filters could simplify the complexity of the current superheterodyne architecture. In this paper, the design of a Single Pole Double Throw (SPDT) switch using 0.35μm Complementary Metal Oxide Semiconductor (CMOS) technology is discussed. The SPDT RF CMOS switch was then simulated in the range of frequency of 0-2GHz. At 2 GHz, the switch exhibits insertion loss of 1.153dB, isolation of 21.24dB, P1dB of 21.73dBm and IIP3 of 26.02dBm. Critical RF T/R switch characteristic such as insertion loss, isolation, power 1dB compression point and third order intercept point, IIP3 is discussed and compared with other type of switch designs. Pre and post layout simulation of the SPDT RF CMOS switch are also discussed to analyze the effect of parasitic capacitance between components’ interconnection.